T&T Clark handbook to the historical Paul - Schellenberg, Ryan S.; Wendt, Heidi, 1982- (London ; New York : T&T Clark, 2022)
"Reconsiders Paul's life including his literacy, social location and place within Judaism, surveys all the literary and historical sources, and reconstructs potential "micro-biographies" from the texts associated with Paul"--
Sources and Methodology -- Biographical Problems -- Epistolary Micro-Biographies.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Paul, -- the Apostle, Saint; Apostles -- Biography; Biographies